The Effectiveness of maternal influenza vaccination in protecting neonates from respiratory infections - Fartun Mohamed; ZamZam Mohammed; Abdirasak Ali; Kizito Bello; Yahye Nageye (Microbes and Infectious Diseases, 2025)
Background: Maternal influenza vaccination is a vital public health strategy that safeguards both pregnant women and their newborns against severe respiratory infections. Influenza during pregnancy increases the risk of complications, including hospitalization and adverse neonatal outcomes. This review evaluates the effectiveness of maternal influenza immunization in reducing neonatal respiratory infections by enhancing passive immunity. It examines the mechanisms of transplacental antibody transfer, which provide early-life protection for infants who are highly susceptible to severe influenza-related complications. Evidence from clinical trials and large-scale vaccination programs demonstrates significant reductions in influenza-related morbidity among neonates born to vaccinated mothers. Despite these benefits, maternal influenza vaccine uptake remains suboptimal due to concerns about vaccine safety, limited awareness, and healthcare access barriers. Addressing these challenges requires targeted public health interventions, including educational campaigns, healthcare provider recommendations, and policy initiatives aimed at increasing accessibility and acceptance of maternal immunization. Strengthening global efforts to improve maternal vaccination coverage can substantially reduce the burden of neonatal respiratory infections, decrease healthcare costs, and enhance overall maternal and infant health outcomes. By reviewing current evidence and identifying strategies for improvement, this paper underscores the critical role of maternal influenza vaccination in protecting the most vulnerable populations.